Penerapan Metode Penemuan Terbimbing pada Pembelajaran Matematika - Nasution, Melda; Mulyono, Dodik; Purwasi, Lucy Asri (JOEAI (Journal of Education and Instruction), 2018)
The purpose of this study was to apply the guided discovery method in mathematics learning for eighth grade students of SMP Muhammadiyah 2 Tugumulyo. The research method used was the quasi-experimental method (Quasi experiment) which was carried out in one experimental class without a comparison group (control group). The population is all students of class VIII SMP totaling 127 students, and as a sample is class VIII.b which is taken randomly by means of the draw. Data analysis using t test, obtained thit = 2.92> ttab = 1.69, so that students' mathematics learning outcomes after the implementation of the guided discovery method is complete. The average score of students' mathematics learning using the guided discovery method is 80.80. Conclusion, the application of guided learning methods is very appropriate in mathematics learning. Keywords: Learning Outcomes, Mathematics, Discovery Learning Methods.